Preparation method and application of magnetic aminated high-crosslinking adsorption resin
The magnetic amination highly crosslinked resin synthesized by oleic acid double-layer coating of Fe3O4 magnetic beads and using suspension polymerization-amination-post-crosslinking process, the corrosion and pore blockage of magnetic highly crosslinked adsorption resin during the preparation process is solved. The problem is to achieve efficient removal of heavy metal ions and aromatic ol composite pollutants in water.
Patent Information
- Application Number
- CN202411732359.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing magnetic highly crosslinked adsorption resins have magnetic particles corrosion and pore blockage during the preparation process, resulting in low adsorption capacity and poor kinetic performance, making it difficult to effectively remove heavy metal ions and aromatic phenolic composite pollutants in water.
Fe3O4 magnetic beads were coated with oleic acid, and a magnetic amination-post-crosslinking resin (YQ-2) was synthesized through suspension polymerization-amination-post-crosslinking process. This resin has rich pore structure and high specific surface area. It can efficiently adsorb heavy metal ions and aromatic pollutants.
It has achieved in-depth treatment of heavy metal ions and aromatic phenolic composite pollutants in water, improved adsorption efficiency and kinetic performance, and is suitable for the removal of pollutants in complex water bodies.
Smart Images

Figure CN119219822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection and discloses a preparation method and application of a magnetic aminated highly cross-linked adsorption resin. Background Art
[0002] Heavy metals refer to metal elements with a density greater than 5.0g / cm3, mainly including copper, lead, zinc, tin, nickel, cobalt, antimony, mercury, cadmium, bismuth and other metal elements, as well as arsenic and other metalloid elements with significant biological toxicity. As important raw materials for industrial and technological development, these heavy metals are widely used in industries such as electronic electroplating, mining and smelting, papermaking, power generation and anti-corrosion. The illegal and excessive discharge of these industrial wastewater, waste residues and waste gases will inevitably cause harm to environmental safety and human health. Heavy metals entering the water environment are difficult to biodegrade, but are easily adsorbed in water sediments. They can also be enriched in organisms through the food chain, react with proteins and enzymes in the body to inactivate them, and can also accumulate in the human body to cause chronic poisoning. Most heavy metal elements have the characteristics of high toxicity, high water solubility, easy diffusion, and long pollution duration. Even low concentrations will still threaten water environment safety and human health. Among these heavy metal pollutions, copper, lead and zinc have become typical heavy metal pollutants in water environment pollution due to their large dosage, wide application and high pollution level. Studies have shown that Cu(II), Pb(II) and Zn(II) pollution has been detected in surface water, groundwater ecosystems and even drinking water systems. Copper and zinc are both essential trace elements for the human body, but if the concentration in the water environment is high and exceeds the maximum threshold, it will endanger the health of organisms. If the lead content exceeds 5 mg / kg, it will cause poisoning, diarrhea and vomiting, and damage the nervous system and reproductive system. In severe cases, it will endanger life and health. In view of the harmfulness of copper, lead and zinc pollution, my country has given clear regulations on the emission standards and limit values of domestic water standards for these three heavy metal elements.
[0003] Phenol refers to a compound with a hydroxyl group attached to its benzene ring structure. Such compounds generally have an aromatic smell, so they are also called aromatic phenol compounds. The benzene ring structure in aromatic phenol compounds is highly stable, but the introduction of hydroxyl groups increases the electron cloud density of the benzene ring and enhances the chemical reactivity. Aromatic phenol compounds with strong reactivity are important raw materials in industrial production and are widely used in industries such as pesticides, dyes, medicines, coking, resins and electroplating. These industries will produce a large amount of wastewater, waste gas and waste residue containing aromatic phenols during production and use. If these wastewater, waste gas and waste residues are not treated, they will undoubtedly cause serious harm to the ecological environment if they are illegally discharged or used to irrigate farmland. Aromatic phenol contains a hydroxyl structure and has a greater solubility than other aromatic compounds. It is easier to remain in water bodies and is one of the most common and most harmful organic pollutants in water bodies. Aromatic phenol compounds are highly toxic and enter the body of organisms through different pathways. They are difficult to degrade and can interact with the protein of organisms, endangering the immune and endocrine systems of organisms and even causing death. Relevant toxicological studies have shown that low concentrations of phenol in the water environment can cause cumulative chronic poisoning and affect the growth and development of aquatic organisms. When the concentration of phenol in the water environment exceeds 0.5 mg / L, it will cause poisoning. For example, oral intake of 1g of phenol will cause death. In view of the characteristics of aromatic phenol compounds such as high toxicity, difficulty in degradation, and easy accumulation, environmental protection departments in many countries such as the United States and Germany have listed them as priority pollutants and strictly controlled emission standards. my country has also listed phenol, m-cresol, 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol, and p-nitrophenol as priority control pollutants. At the same time, strict emission standards are also implemented, stipulating that the emission of volatile phenolic organic matter should be less than 0.5 mg / L, and the concentration of phenolic organic matter in drinking water should be less than 0.001 mg / L.
[0004] Heavy metal ions and aromatic pollutants are typical toxic composite pollutants of inorganic and organic types. They have a wide range of sources, are persistent and mobile, and are easy to form composite pollutants. Therefore, it is impossible for the actual polluted water to contain only a single heavy metal or phenolic organic pollutant, but usually exists in the form of heavy metal-aromatic phenol composite pollutants. Due to the characteristics of their own processes, the production wastewater discharged by industries such as printing and dyeing, petroleum refining, electroplating, pharmaceuticals, metal beneficiation and smelting often contains heavy metal ions, aromatic compounds and high concentrations of inorganic salts. At the same time, the emission of automobile exhaust and industrial waste gas, the combustion of fuels and the incineration of garbage may also cause volatile phenolic organic matter and metal ions to form composite pollutants. Composite pollutants in the atmosphere are deposited on the surface through dry and wet sedimentation, and then collected into the water environment in the form of equal migration of surface runoff. Usually, the two pollutants can be detected in the catchment area, and then enter the soil, sediment, and even the groundwater environment through infiltration and downward migration. When heavy metal ions and phenolic pollutants exist in the water environment at the same time, the two pollutants may interact with other substances in the environment in various complex ways. The toxicity of compound pollution is also more complex, and there may be a joint effect, resulting in greater toxicity of compound pollutants, which may bring greater harm to the ecological environment and life and health. In summary, human activities, agricultural and industrial development allow metal ions and aromatic phenol pollutants to enter the water environment simultaneously or successively through multiple pathways. Heavy metals and aromatic phenols are typical pollutants in water bodies, and the two may also cause compound pollution. Compared with single pollutants, compound pollution is more toxic and more difficult to control, and it is an environmental problem that needs to be solved urgently. Therefore, it is crucial to conduct in-depth and systematic comparative studies on the mechanism of action of single and compound pollution and explore technologies that can control both single pollutants and compound pollution. Heavy metal and aromatic phenol pollutants have the characteristics of extensiveness, toxicity, accumulation and persistence. The treatment technology of complex wastewater containing heavy metals and aromatic phenols has also become a new environmental hotspot.
[0005] At present, the treatment technologies for heavy metal and aromatic phenol pollution include biotechnology, physical technology, chemical technology and combined treatment technology. Among them, the widely used treatment methods mainly include: chemical precipitation, membrane separation, oxidation, biological treatment and adsorption. Compared with treatment technologies such as precipitation and oxidation, adsorption has become an advantageous technology for the current control of water pollutants because of its simple and economical, small secondary pollution and recyclable characteristics. Among the many adsorption materials, adsorption resins have become popular adsorption materials in pollution remediation technology due to their environmental friendliness, large adsorption capacity and ability to enrich and recover specific adsorbents. Adsorption resins are polymers with specific functional groups and porous three-dimensional structures obtained by polymerization of monomers and porogens, and have the effect of enriching and separating pollutants. The development and application of adsorption resins has a history of nearly a hundred years. After continuous improvement and optimization by researchers, traditional adsorption resins have gone through the development of gel-type and macroporous ion exchange resins, chelating adsorption resins, ultra-high cross-linking resins, and nano-magnetic adsorption resins. The current research is aimed at a specific adsorbent system, and through structural design and modification of the adsorption resin, a new type of composite adsorption resin with selectivity, high efficiency and practicality is prepared. Commonly used macroporous resins are polystyrene resin and polyacrylate resin, with the following chemical structures: .
[0006] Although macroporous ion exchange resins have cross-linked structures, good mechanical strength, stable chemical properties and other characteristics, and can remove various ionic pollutants based on their exchange principle, they lack adsorption selectivity. Heavy metal ions in water bodies often coexist with other inorganic metal salt ions, and the composition of wastewater is complex, often containing acids, alkalis, or high salts. Therefore, ion exchange resins cannot effectively remove heavy metal ions in complex water bodies. Although ultra-high cross-linked adsorption resins have a high adsorption capacity for organic pollutants, there are still the following key restrictive issues in their actual use. Due to the poor hydrophilicity of polystyrene ultra-high cross-linked resins, they often need to be pre-treated with polar solvents in actual applications. The process is cumbersome and the cost is increased, and the selectivity is poor. In addition, the pore structure of ultra-high cross-linked resin is mainly distributed in nanometer-scale micropores, the adsorption rate is slow, the kinetic performance is poor, and the pore blocking phenomenon is easy to occur in the later stage of adsorption. The particle size of ultra-high cross-linked adsorption resin is generally between 500-1000 microns, and the particle size is large. It can often only be operated using a fixed bed, which is costly, slow, and has a small amount of water to be treated. The water quality of the effluent cannot be adjusted. This is also a key problem that limits the practicality of ultra-high cross-linked resins. At present, most of the synthesized and applied magnetic adsorption resins are magnetic ion exchange resins, which have a good removal effect on metal ions in water bodies. However, the magnetic ion exchange resin has a low specific surface area and a single pore structure, and the adsorption efficiency of organic pollutants is not high. It is difficult to achieve efficient treatment of wastewater containing both ionic heavy metal pollutants and aromatic phenol organics. At present, the preparation of magnetic highly cross-linked adsorption resins is mainly limited by two aspects: first, the key steps in the synthesis process of highly cross-linked adsorption resins, chloromethylation and post-cross-linking processes are both acidic environments, which are highly corrosive to magnetic particles, making it difficult to copolymerize and embed magnetic particles. Secondly, there are many microporous structures in ultra-high cross-linked resins, but the particle size of nanomagnetic particles is generally larger than the micropore size, making it difficult for them to be effectively deposited in the micropores, and the micropores are prone to pore blockage, which reduces the adsorption capacity. In view of this, studying new preparation processes and synthesizing magnetic highly cross-linked nano-resins modified with functional groups and having suitable pore size structures is a key issue in promoting the application of magnetic resins in the treatment of actual wastewater pollution. Summary of the invention
[0007] The purpose of the present invention is to provide a preparation method and application (i.e. purpose) of a magnetic aminated highly cross-linked adsorption resin. The magnetic highly cross-linked adsorption resin prepared by the preparation method of the present invention has a large number of macropores and a small number of micropores by introducing aminated groups. The aminated groups can be used to adsorb heavy metal ions in water and aromatic phenol organic pollutants in water, and are particularly suitable for the effective adsorption and removal of composite pollutants of heavy metal ions and aromatic phenols in water.
[0008] A method for preparing a magnetic highly cross-linked adsorption resin of the present invention comprises the following steps: 1) Dissolve ferric chloride hexahydrate and ferric chloride tetrahydrate in deionized water, heat to 70-90°C, add ammonia water, and drop acetone mixed with oleic acid to react for 5-15 minutes, then drop oleic acid to react, and separate the monolayer oleic acid-modified Fe3O4 nanoparticles after the reaction is complete; 2) Mix the monolayer oleic acid-modified Fe3O4 nanoparticles with ammonia water, add oleic acid under nitrogen atmosphere, heat to 70-90°C, react for 25-35 minutes, cool and add a small amount of dilute hydrochloric acid for precipitation and separation to obtain double-layer oleic acid-modified Fe3O4 nanoparticles; 3) Mixing a dispersed phase consisting of an aqueous solution of gelatin, polyvinyl alcohol, sodium sulfate and lauryl sulfuric acid with an oil phase consisting of divinylbenzene (DVB), double-layer oleic acid-modified Fe3O4 nanomagnetic beads, porogen n-hexane and initiator benzoyl peroxide, stirring at 70-90°C under nitrogen protection, and performing suspension polymerization. After the reaction is completed, cooling, separating the precipitate, washing the solid with hot water, and drying, a magnetic cross-linked resin (i.e., a magnetic cross-linked macroporous polystyrene resin, named YQ-1 resin) is obtained. 4) The magnetic cross-linked resin obtained in the previous step is swollen in toluene, and then ethylenediamine solution is added, stirred, and heated to 60-70° C., and the reaction is completed to obtain a magnetic aminated cross-linked resin; 5) After swelling the magnetic aminated cross-linked resin in 1,2-dichloroethane, add FeCl3, stir and reflux at 60-70°C for 0.5-2 hours, heat to 80-90°C, stir and reflux for 4-6 hours, cool after the reaction, separate the resin, and obtain a magnetic aminated highly cross-linked adsorption resin (named YQ-2 resin).
[0009] In some embodiments, in the preparation method of the present invention, in step 1), the temperature is 80° C., the oleic acid addition rate is 1 g / 5 min, and the reaction is carried out for at least 30 min after the oleic acid is added.
[0010] In some embodiments, in the preparation method of the present invention, in step 1), Fe 2+ :Fe 3+ The molar ratio of Fe is 1:2. 2+ : The molar ratio of to ammonia water is 5:(1-2).
[0011] In some embodiments, in the preparation method of the present invention, in step 1), the mass ratio of oleic acid to ferric chloride tetrahydrate is 1:1, wherein the mass ratio of the oleic acid in the acetone to the subsequently added oleic acid is 1:4.
[0012] In some embodiments, in the preparation method of the present invention, in step 2), the amount of oleic acid is equivalent to the total amount of oleic acid added in step 1). In some embodiments, in the preparation method of the present invention, in step 2), the reaction temperature is 80° C. and the reaction time is 30 min.
[0013] In some embodiments, in the preparation method of the present invention, in step 3), in the dispersed phase, the weight ratio of gelatin, polyvinyl alcohol, sodium sulfate and lauryl sulfuric acid is 2:2:0.1:0.1; in the oil phase, the mass ratio of chloromethylstyrene, divinylbenzene, double-layer oleic acid-modified Fe3O4 nanomagnetic beads, n-hexane and benzoyl peroxide is 45:5:4:30:0.6, and the reaction temperature is preferably 90°C.
[0014] In some embodiments, in the preparation method of the present invention, in step 4), the mass volume ratio of the magnetic cross-linked resin to ethylenediamine is 1:4 g / ml.
[0015] In some embodiments, in the preparation method of the present invention, in step 4), the reaction temperature is 62° C. and the reaction time is 6 hours.
[0016] In some embodiments, in the preparation method of the present invention, in step 5), the mass ratio of the magnetic cross-linked resin to FeCl3 is 25:3.
[0017] In some embodiments, in the preparation method of the present invention, in step 5), FeCl3 is added, and the mixture is stirred and refluxed at 62°C for 1 hour, then the temperature is slowly raised to 90°C, and the stirring and reflux reaction is continued for 5 hours. After the reaction is completed, the resin is cooled and separated, washed to neutrality, and then dried.
[0018] In some embodiments, in the preparation method of the present invention, in step 5), a sodium hydroxide solution is further added to neutralize the HCl produced by the reaction.
[0019] In another embodiment, the present invention provides a magnetic aminated highly cross-linked adsorption resin prepared by the above preparation method.
[0020] In another embodiment, the present invention provides the use of the magnetic highly cross-linked adsorption resin prepared by the preparation method of the present invention for adsorbing and removing heavy metal ions and / or aromatic phenol pollutants, especially removing heavy metal ion pollutants and aromatic phenol complex pollutants in water.
[0021] Specifically provided is the application of the magnetic highly cross-linked adsorption resin prepared by the preparation method of the present invention in adsorbing and removing heavy metal ions and / or aromatic phenol pollutants in water, especially in removing heavy metal ion pollutants and aromatic phenol composite pollutants in water.
[0022] Preferably, the heavy metal ion is one or more of Cu(II), Pb(II) and Zn(II), and the aromatic phenol is one or more of phenol (PN), hydroquinone (HN) and p-nitrophenol (PNP). The preparation method of the present invention embeds the ultra-high cross-linked adsorption resin with functional groups (amine groups) into magnetic Fe3O4 nanoparticles through a specific preparation method, and the obtained magnetic aminated high cross-linked resin has rich pore structure, high specific surface area and surface functional groups, and can efficiently remove phenolic organic pollutants.
[0023] The preparation method of the present invention adopts a double-layer coating of Fe3O4 with oleic acid to synthesize Fe3O4 magnetic beads resistant to acid corrosion, and then performs suspension polymerization reaction with chloromethylvinylbenzene (VBC) and divinylbenzene (DVB): "suspension polymerization-amination-post-crosslinking" to synthesize a magnetic aminated high cross-linked resin (marked as YQ-2 resin) with a higher specific surface area and richer microporous structure. The YQ-2 resin mainly relies on hydrophobic and π-π effects to adsorb phenolic pollutants, and relies on amino groups as complexing groups to complex metal ions to achieve the function of adsorbing heavy metal ions. The adsorption of PN, HN and PNP by the YQ-2 resin gradually increases with the increase of NaCl concentration and pH. Typical chemical tail waters such as printing and dyeing, electroplating and pharmaceuticals often contain heavy metal ions, aromatic phenols and inorganic salts at the same time. Therefore, the YQ-2 resin of the present invention is particularly suitable for the removal of phenolic pollutants in salt-heavy wastewaters in these industries, and the YQ-2 resin also has a very high adsorption effect on heavy metal ions. Although YQ-3 has a higher specific surface area and micropore area ratio, and has strong adsorption for aromatic phenols, it has no complexing groups and can only weakly adsorb metal ions through cation-π bonds, and its adsorption for metal ions is limited. YQ-2, on the other hand, exhibits a strong adsorption effect on metal ions through complex adsorption with aminated groups. Therefore, compared with YQ3 resin, YQ2 resin not only has a strong adsorption capacity for aromatic phenol organic matter, but also has a very high adsorption for metal ions. The method of the present invention uses a secondary oleic acid double-layer coating to make Fe3O4 nanoparticles more stable, and has better dispersion and anti-corrosion effects. The magnetic cross-linked resin YQ-2 prepared by the present invention can be applied to a fully mixed contact tank process to achieve in-depth treatment of the complex pollution of heavy metal ions and aromatic phenols in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) is a sample picture of double-layer oleic acid-modified Fe3O4 particles and double-layer oleic acid-coated Fe3O4, and (b) is its infrared spectrum.
[0025] Figure 2 TEM morphology and diffraction patterns of double-layer oleic acid-modified Fe3O4, where (a) is the morphology of 50 nm, (b) is the morphology of 10 nm, and (c) is the TEM image of double-layer oleic acid-modified Fe3O4 particles.
[0026] Figure 3 Transmission electron microscope energy spectrum scan of double-layer oleic acid-modified Fe3O4 particles, where (a) is the EDS energy spectrum (surface scan) and (b) is the EDS surface scan element distribution map.
[0027] Figure 4 XRD diffraction patterns of double-layer oleic acid-modified Fe3O4 particles before and after.
[0028] Figure 5 (a) is the hysteresis loop of Fe3O4 particles without oleic acid modification, single-layer oleic acid modification and double-layer oleic acid modification; (b) is the content curve of free Fe ions under different acidic conditions.
[0029] Figure 6 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of YQ-1, YQ-2 and YQ-3 resins, among which a(1) is the SEM image of YQ-1 resin magnified 200 times, a(2) is the SEM image of YQ-1 resin magnified 10000 times, a(3) is the SEM image of YQ-1 resin magnified 100000 times, a(4) is the TEM image of YQ-1 resin, b(1) is the SEM image of YQ-2 resin magnified 200 times, b a (2) is the SEM image of YQ-2 resin magnified 10,000 times, b (3) is the SEM image of YQ-2 resin magnified 100,000 times, b (4) is the TEM image of YQ-2 resin, c (1) is the SEM image of YQ-3 resin magnified 200 times, c (2) is the SEM image of YQ-3 resin magnified 10,000 times, c (3) is the SEM image of YQ-3 resin magnified 100,000 times, and c (4) is the TEM image of YQ-3 resin.
[0030] Figure 7 : The hysteresis loop diagram of the resin, where (a) is the saturation magnetization intensity diagram of the three resins YQ-1, YQ-2 and YQ-3, and (b) is the saturation magnetization intensity diagram of the YQ-2 and YQ-3 resins after being treated with different concentrations of hydrochloric acid.
[0031] Figure 8 XRD diffraction patterns of YQ-2 and YQ-3 resins.
[0032] Fig. 9 The infrared spectra and XPS spectra of the resins are shown in Figure 2, where (a) is the infrared spectra of YQ-1, YQ-2 and YQ-3 resins, (b) is the XPS spectra of YQ-2 and YQ-3 resins, and (c) is the energy spectrum peak fitting diagram of N1s.
[0033] Fig.10(a) is a curve diagram showing the effect of the dosage of YQ-2 and YQ-3 resins on the adsorption performance of Cu(II); (b) is a curve diagram showing the effect of the dosage of YQ-2 resin on the adsorption performance of Pb(II) and Zn(II).
[0034] Fig.11 The figure shows the adsorption curves of YQ-2 and YQ-3 resins for metal ions, where (a) is the adsorption graph of YQ-2 resin for Cu(II), Pb(II) and Zn(II) in solution under different pH environments, and (b) is the adsorption graph of YQ-2 and YQ-3 resins for Cu(II), Pb(II) and Zn(II) in solution under different pH environments.
[0035] Fig.12 The figure shows the effect of salt concentration on the adsorption performance of metal ions on YQ-2 and D001 resins, where (a) is the adsorption performance of YQ-2 resin for heavy metal ions when sodium salt and calcium salt of different concentrations coexist, and (b) is the adsorption performance of YQ-2 resin and D001 commercial resin for Cu(II) when sodium salt or calcium salt coexists.
[0036] Fig.13 The figure shows the influence of the dosage of YQ-2 and YQ-3 resins on the adsorption performance of phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP), among which (a) is the influence of the dosage of YQ-3 resin on the adsorption effect of the three phenols, and (b) is the influence of the dosage of YQ-2 resin on the adsorption effect of the three phenols.
[0037] Fig.14 The graphs show the relationship between pH value and the adsorption of PN, RN and PNP by YQ-2 and YQ-3 resins. (a) shows the adsorption performance of three phenols in solution by YQ-3 resin under different pH conditions, and (b) shows the adsorption performance of three phenols in solution by YQ-2 resin under different pH conditions.
[0038] Fig.15 Figure 2 is the effect of YQ-2 and YQ-3 resins on the adsorption performance of PN, HN and PNP under different salt concentrations, where (a) is the adsorption performance of YQ-2 resin on PN, HN and PNP when it coexists with different concentrations of NaCl, and (b) is the adsorption performance of YQ-3 resin on PN, HN and PNP when it coexists with different concentrations of NaCl.
[0039] Fig.16 The adsorption curve of Cu(II) and PNP by YQ-2 resin under different pH conditions.
[0040] Fig.17(a) is the effect of YQ-2 resin on PNP adsorption under different concentrations of Cu(II) pre-adsorption, and (b) is a comparison of the adsorption amount of PNP by YQ-2 pre-loaded with Cu(II) and YQ-2 resin.
[0041] Fig.18 (a) is the effect of YQ-2 resin on Cu(II) adsorption under different concentrations of PNP pre-adsorption, and (b) is a comparison of the adsorption amount of Cu(II) by YQ-2 pre-loaded with PNP and YQ-2 resin.
[0042] Fig.19 (a) is the Langmuir and Freundlich model fitting curve diagram of Cu(II) adsorption on YQ-2 resin, and (b) is the Langmuir and Freundlich model fitting curve diagram of PNP adsorption on YQ-2 resin.
[0043] Fig. 20 This is the regeneration performance diagram of YQ-2 resin after adsorption of Cu(II) and PNP composite pollution. DETAILED DESCRIPTION
[0044] The following examples are merely representative and are used to further understand and illustrate the essence of the present invention, but are not intended to limit the scope of the present invention in any way.
[0045] Example 1 Synthesis of double-layer oleic acid-coated nano-Fe3O4 1. Synthesis of Fe3O4 nanoparticles (microparticles): Synthesis of Fe3O4 nanoparticles by coprecipitation method Dissolve 27.42 g of ferric chloride hexahydrate and 10.07 g of ferric chloride tetrahydrate in 500 ml of deionized water (Fe 2+ :Fe 3+ =1:2), placed in a 1L three-necked round-bottom flask, the mixed solution was placed under nitrogen for 30 min to remove dissolved oxygen, then heated to 80 °C, and 100 mL of ammonia water (25 wt%) was quickly poured into it while stirring for co-precipitation reaction. After 1 hour, the magnetic precipitate was separated by a permanent magnet, dried and ground to obtain Fe3O4 nanoparticles (referred to as Fe3O4 nanoparticles).
[0046] 2. Synthesis of monolayer oleic acid-modified Fe3O4 nanoparticles Synthesis of monolayer oleic acid-modified Fe3O4 nanoparticles by coprecipitation method Dissolve 27.42 g of ferric chloride hexahydrate and 10.07 g of ferric chloride tetrahydrate in 500 ml of deionized water (Fe 2+ :Fe 3+=1:2), placed in a 1L three-necked round-bottom flask, the mixed solution was placed under nitrogen for 30 minutes to remove dissolved oxygen, then the temperature was raised to 80°C and 100mL of ammonia water (25wt%) was quickly added while stirring, and 10mL of acetone containing 2g of oleic acid was dropwise added to carry out a coprecipitation reaction. After reacting for 10 minutes, 8g of oleic acid was dropwise added at a rate of 1g of oleic acid / 5min, and the reaction was continued for more than 30 minutes. After separation and washing with a permanent magnet, magnetic particles, i.e., single-layer oleic acid-modified Fe3O4 nanoparticles, were obtained.
[0047] 3. Synthesis of double-layer oleic acid-coated Fe3O4 magnetic nanoparticles The single-layer oleic acid-modified Fe3O4 nanoparticles prepared in 2 were mixed with 100 mL of ammonia water (15 wt%), and 10 g of oleic acid was added under stirring under nitrogen atmosphere, and the mixture was heated to 80 °C for reaction for 30 min. After cooling, a small amount of dilute hydrochloric acid was added under continuous stirring for precipitation and separation, and then washed repeatedly with water and methanol to obtain double-layer oleic acid-modified Fe3O4 nanomagnetic beads (i.e., double-layer oleic acid-coated Fe3O4 nanomagnetic beads). Finally, the Fe3O4 nanomagnetic beads were dissolved and dispersed in n-hexane for further use. The reaction formula is as follows: , .
[0048] Advantages of double-layer oleic acid coated Fe3O4 nanoparticles: Fe 2+ and Fe 3+ Nano-Fe3O4 was synthesized by coprecipitation under the condition of excess OH-. However, the particles were affected by electrostatic force (Fe 2+ and Fe 3+ and extranuclear OH -), surface energy, and van der Waals forces make it easy to agglomerate, increase the weight of Fe3O4 particles, reduce the surface area and use efficiency. The agglomeration phenomenon can be effectively reduced by adding surfactant oleic acid for surface modification. Oleic acid undergoes chemical and physical adsorption on the surface of Fe3O4 particles and coats Fe3O4 nanoparticles. This steric hindrance effect makes the nanoparticles dispersed and stable, thereby reducing agglomeration. The addition method and amount of oleic acid will affect the particle size and stability of nano-Fe3O4. At present, oleic acid modification mainly adopts the coprecipitation method to prepare nano-Fe3O4 particles, and then adds oleic acid for surface modification. In this study, oleic acid was added dropwise at the initial stage of the formation of nano-Fe3O4 crystal phase to react, and oleic acid was coated while the nano-Fe3O4 grains grew to prevent Fe3O4 particles from agglomerating, effectively controlling the particle size of the particles. The amount of oleic acid is another key factor affecting the particle size and stability of nano-Fe3O4. If the amount of oleic acid is small, the nano-Fe3O4 particles cannot be completely coated and a dense coating layer cannot be formed. In order to improve the stability and acid corrosion resistance of nano Fe3O4, the present invention adopts the process of secondary double-layer coating of oleic acid. During the single-layer coating, the carboxyl group in the oleic acid and the hydroxyl group of the nano Fe3O4 form an oil film structure with the carboxyl group facing inward and the long-chain alkyl facing outward through hydrogen bonding. The single-layer oil film structure can make the nano Fe3O4 stably dispersed, and also make the Fe3O4 particle surface lipophilic. When the oleic acid double-layer coating is added again, the hydrophobic end long-chain alkyl of oleic acid moves to the surface of the Fe3O4 microparticles coated with the single layer, and forms a mutually entangled interlaced chain structure by relying on the hydrophobic-hydrophobic physical adsorption. The physical adsorption of the second layer compresses the first layer, so that oleic acid is more densely wrapped on the surface of the magnetic nanoparticles. This double-layer oleic acid steric hindrance and electrostatic repulsion make the nano Fe3O4 more stable, and the dispersion effect and anti-corrosion effect are better, which is conducive to the subsequent use of the acidic environment suspension polymerization to synthesize the magnetic high cross-linked adsorption resin.
[0049] Example 2 Characterization of double-layer oleic acid Fe3O4 nanoparticles 1. Using infrared to test Fe3O4 nanoparticles and double-layer oleic acid Fe3O4 nanoparticles, the results are as follows Figure 1 shown. Figure 1 (a) is the appearance of the microparticles. It can be seen that the black Fe3O4 nanoparticles are stratified and then settled in the water. When an external magnetic field is applied, the Fe3O4 particles are quickly attracted and separated. The oleic acid-modified Fe3O4 is stably dispersed in n-hexane and appears as a stable reddish-brown suspension. Figure 1 The black line in (b) is the infrared spectrum of Fe3O4 nanoparticles at 580.27 cm -1 The characteristic peak is the Fe-O vibration absorption peak, which has a high peak value and obvious infrared characteristics. -1The characteristic peak is the infrared absorption peak of -OH, which is the hydroxyl group adsorbed on the surface of Fe3O4 nanoparticles. The red line in the figure is the infrared spectrum of double-layer oleic acid-modified Fe3O4 nanoparticles, at 2923.49 cm -1 and 2854.09cm -1 The vibration peaks of -CH3 and -CH2 appeared at 1711.56cm -1 and 1283.27cm -1 There are obvious characteristic absorption peaks of C=O and CO at 1459.71 cm -1 and 940.83cm -1 The characteristic absorption peaks are the out-of-plane and in-plane vibration peaks of the hydroxyl group. Compared with the infrared spectrum before modification, the Fe-O absorption peak after modification is weakened and changes from 580.27 cm -1 Shift to 600.95cm -1 This may be due to the chemical adsorption of -COO in Fe3O4 nanoparticles and oleic acid. All these prove that oleic acid is successfully coated and there is a chemical bond between Fe3O4 nanoparticles. -1 、1520.05cm -1 and 1329.43cm -1 An absorption peak band appeared, which was due to the two symmetric and antisymmetric -C=O vibration peaks formed by the -COO of the outer layer of oleic acid. This also proved that oleic acid successfully modified the Fe3O4 nanoparticles by double-layer coating. This peak band did not appear in the infrared spectrum of single-layer oleic acid coating.
[0050] 2. Stability test In order to further verify the stability and corrosion resistance of oleic acid modified nano-Fe3O4 particles, TEM, XRD, magnetic properties and acid leaching experiments were carried out. The results are as follows. Figure 2 TEM morphology and diffraction pattern of Fe3O4 nanoparticles modified with oleic acid double layer. Figure 2 (a) 50nm and Figure 2 (b) The 10nm morphology shows that the double-layer oleic acid-coated Fe3O4 is approximately spherical, with a particle size between 8-15nm, clear spacing between particles, and uniform dispersion without agglomeration. Compared with the unmodified Fe3O4 nanoparticles, the dispersibility is significantly improved. From the TEM diffraction Figure 2 (c) It can be seen that the double-layer oleic acid-coated Fe3O4 nanoparticles have a polycrystalline structure.
[0051] Transmission electron microscope energy spectrum scanning test of double-layer oleic acid-modified Fe3O4. The results are as follows Figure 3As shown in Figure (a), the double-layer oleic acid-coated Fe3O4 nanoparticles are evenly dispersed without agglomeration. EDS energy spectrum can be used for semi-quantitative analysis of elemental composition. Oleic acid-modified Fe3O4 contains C, H, O and Fe. C, O and Fe (H cannot be detected) are detected in the EDS energy spectrum of Figure (b), with the content of C element accounting for 96.5% and the content of O element accounting for 2.7%, indicating that oleic acid has been successfully coated on the Fe3O4 particles.
[0052] XRD diffraction test of nano-Fe3O4 and double-layer oleic acid-modified Fe3O4 particles, the results are as follows Figure 4 As shown in the figure, there are 8 significant diffraction peaks of Fe3O4 nanoparticles at 18.24°, 30.04°, 35.40°, 37.08°, 43.10°, 53.38°, 56.92° and 62.50°, which correspond to (111), (220), (311), (400), (422), (511), (440) and (533) respectively by comparing with the standard Fe3O4 diffraction spectrum, indicating that they are Fe3O4 nanocrystals with inverse spinel structure. The 8 diffraction peaks have good intensity and clear peak shape, indicating that the material has good crystallinity. The XRD diffraction peaks of oleic acid-modified Fe3O4 are consistent with the position of nano-Fe3O4, and the intensity of the diffraction peaks is weakened. After modification, the hydrogen bonding between the hydroxyl and carbonyl groups of the double-layer oleic acid weakens the crystallinity of the nano-magnetic ions, but does not change the crystal form of the nano-Fe3O4 particles.
[0053] The hysteresis loop test and stability test of Fe3O4, the results are as follows Figure 5 shown.
[0054] Figure 5 (a) shows the hysteresis loops of nano-Fe3O4 and oleic acid-modified Fe3O4. The saturation magnetization of Fe3O4 without oleic acid coating, single-layer oleic acid coating and double-layer oleic acid coating are 45.8emu / g, 32.1emu / g and 29.5emu / g respectively. The remanence and coercive force of the three are basically zero, and all maintain superparamagnetism. Oleic acid coating does not change the paramagnetism of Fe3O4 nanoparticles, but reduces the saturation magnetization. This is because the oleic acid coating layer improves the corrosion resistance and oxidation resistance of Fe3O4 nanoparticles and enhances the stability of Fe3O4 nanoparticles. Since the post-crosslinking process of the synthesis of highly cross-linked resin is acidic, a leaching test under acidic conditions was carried out to evaluate the acid corrosion resistance of oleic acid-coated Fe3O4 particles.
[0055] Under acidic conditions, the sample was shaken and reacted at 25°C for 12 hours. Figure 5(b) As shown. Oleic acid coating significantly improved the stability of Fe3O4 nanoparticles under acidic conditions. After 12 hours, in a strong acid environment of pH 1.2, 60.4 mg / g of iron ions were detected in the leachate, while under the same experimental conditions, only 4.89 mg / g was detected in the single-layer oleic acid-coated nanoparticles. The iron leaching amount was reduced to 3.32 mg / g when double-layer oleic acid was coated. Double-layer oleic acid coating modification significantly improved the acid corrosion resistance of magnetic nanoparticles.
[0056] Example 3 Synthesis of magnetic cross-linked adsorption resin 1. Synthesis of magnetic cross-linked macroporous polystyrene resin (referred to as magnetic cross-linked resin) In a 1000mL three-necked flask, 500ml of an aqueous solution containing 2g gelatin, 2g polyvinyl alcohol, 0.1g sodium sulfate, and 0.1g lauryl sulfuric acid was added as the dispersed phase, and 45g chloromethylstyrene (VBC), 5g divinylbenzene (DVB), 4g double-layer oleic acid-modified Fe3O4 nanomagnetic beads (double-layer oleic acid nano Fe3O4 microparticles prepared in Example 1), 30.0g porogen n-hexane and 0.6g initiator benzoyl peroxide (approximately 1% of the monomer mass) were mixed as the oil phase. Suspension polymerization was carried out at 80°C and nitrogen protection at a stirring rate of 200rpm for 12h. After cooling, it was separated with a permanent magnet, washed with hot water, filtered and extracted, and finally dried at a temperature of 60°C for 3h. The prepared magnetic cross-linked resin was named YQ-1 resin.
[0057] 2. Synthesis of magnetic aminated highly cross-linked polystyrene resin YQ-2 25.0g YQ-1 magnetic resin was swollen in toluene under nitrogen atmosphere for 4h, and then 100ml ethylenediamine solution was added. At a stirring speed of 400rpm, the temperature was slowly raised to 62℃, and refluxed for 6h, cooled and separated with a permanent magnet, washed to neutrality and then dried. After 25.0g of the above-synthesized resin was swollen in 1,2-dichloroethane under nitrogen atmosphere for 5h, 3.0g FeCl3 was added, stirred and refluxed at 62℃ for 1h, and then slowly heated to 90℃, and continued to stir and reflux for 5h. The released HCl gas was absorbed by NaOH solution (28wt%). After the reaction was completed, the resin was cooled and separated with a permanent magnet, washed to neutrality and then dried to obtain a magnetic aminated highly cross-linked polystyrene resin, named YQ-2 resin.
[0058] 3. Synthesis of magnetic highly cross-linked polystyrene resin YQ-3 (as a comparative resin) After 25.0g YQ-1 magnetic resin was swollen in 1,2-dichloroethane under nitrogen atmosphere for 5 hours, 4.0g FeCl3 was added and stirred for 1 hour, and stirred and refluxed for 4 hours at 62°C, and then slowly heated to 90°C, and stirred and refluxed for 8 hours. The released HCl gas was absorbed by NaOH solution (28wt%). After the reaction was completed, the resin was cooled and separated, washed to neutrality and dried, and named YQ-3 resin, as follows: .
[0059] Example 4 Resin Characterization 1. Appearance: The appearance of the resins YQ-1, YQ-2 and YQ-3 prepared in Example 3 was observed by scanning electron microscopy (SEM) and transmission electron microscopy. Figure 6 shown.
[0060] Figure 6 These are the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of YQ-1, YQ-2 and YQ-3 resins. Both the SEM and TEM images can be used to analyze the surface morphology of the resins.
[0061] From the SEM image, it can be seen that the three resins are spherical or ellipsoidal, with a particle size between 80-150 microns. Due to the combination of magnetic Fe3O4 particles, the resin surface is relatively rough. The SEM image magnified 10,000 times can better observe the mottled texture on the sample surface. The surface of YQ-2 and YQ-3 resins is more compact due to the post-crosslinking process. The surface of YQ-1 macroporous resin has some crack structures, which also proves that the pore size of YQ-1 is larger than that of YQ-2 and YQ-3. The SEM image magnified 100,000 times shows that the inside of the resin is formed by the aggregation of nano-scale particles. The gaps between the particles are the pore structure of the resin. The pore size distribution ranges from a few nanometers to hundreds of nanometers. The pore size of YQ-1 is significantly larger than that of YQ-2 and YQ-3. The post-crosslinking process increases the micropore area of YQ-2 and YQ-3 resins and reduces the pore size.
[0062] From the TEM images of the three resins, we can see many dispersed and agglomerated black spots. These black spots of different sizes may be Fe3O4 nanoparticles, with particle sizes ranging from a few nanometers to tens of nanometers. This is due to the limited domain of the resin pore structure and the stable dispersion of oleic acid-coated Fe3O4. Fe3O4 particles can only exist in the form of dispersed or small clusters, and will not form large aggregate clusters. Both SEM and TEM images show that Fe3O4 magnetic particles are successfully loaded on the resin, and the three resins all meet the characteristics of magnetic nano-adsorption resins.
[0063] 2. Analysis of specific surface area, pore structure parameters and organic elements of resin The specific surface area, pore structure parameters and organic elements of the YQ-1, YQ-2 and YQ-3 resins prepared in Example 3 were analyzed. The results are shown in Table 1. The particle sizes of the three resins are distributed between 80-150 μm. Since the chloromethyl groups on the YQ-1 resin participate in the amination and post-crosslinking reactions, the residual chloromethyl groups are less, and the chlorine content of YQ-2 and YQ-3 decreases. The N content of the YQ-2 resin is 2.38, indicating that the amine groups have been successfully modified on the resin.
[0064] The specific surface area and pore volume of YQ-2 and YQ-3 are greater than those of YQ-1. This is because the chloromethyl groups on the resins bridge with adjacent benzene rings during the secondary crosslinking process of the post-crosslinking reaction, which increases the micropore area, increases the specific surface area, and reduces the pore size. The specific surface area of YQ-3 is greater than that of YQ-2 because YQ-2 undergoes an amination reaction first and then a post-crosslinking reaction, while YQ-3 only undergoes a post-crosslinking reaction. The degree of post-crosslinking of YQ-3 is higher, and the ratio of specific surface area to micropore area increases. The specific surface area of YQ-2 resin reaches 431.6 m 2 / g, although the post-crosslinking increases the micropore area, there are only some micropores in the pore structure, and the main pore structure is mesopore-macroporous structure. However, the pore size structure of the currently traditionally synthesized ultra-high cross-linked resin is mainly micropores. The reason is mainly due to the steric hindrance of the modified ethylenediamine group and the dispersed Fe3O4 nanoparticles to prevent excessive crosslinking, and the Fe3O4 nanoparticles act as inorganic porogens, which is conducive to the formation of meso-macroporous structure. At the same time, the strong acidic environment in the post-crosslinking process can easily form surface meso-macroporous pores due to the local corrosion of Fe3O4 nanoparticles. The high specific surface area of this magnetic resin combined with the meso-macroporous structure is conducive to efficient mass transfer and is a key factor in ensuring high adsorption capacity and fast kinetic rate. The higher specific surface area (431.6m 2 / g), excellent pore structure (mainly medium-large pore structure), with a pore diameter of 7.09nm, which is larger than the radius of hydrated metal ions and aromatic phenol compounds, ensuring that these two adsorbents can diffuse quickly and be efficiently adsorbed in the resin pores.
[0065] Table 1. Organic elements and pore structure analysis of resin 3. VSM analysis of resin The magnetic properties of the YQ-1, YQ-2 and YQ-3 resins prepared in Example 3 were tested by hysteresis loops. Figure 7 As shown. Figure 7As can be seen in (a), the saturation magnetization of the three resins YQ-1, YQ-2 and YQ-3 are 3.04emu / g, 1.93emu / g and 1.72emu / g, respectively. After the amination reaction and post-crosslinking process, the specific saturation magnetization of YQ-2 resin decreases. This is because the swelling process of amination and post-crosslinking causes the pores to swell, resulting in the shedding of some Fe3O4 nanoparticles, and the strong acidic environment of the post-crosslinking reaction process causes local corrosion of Fe3O4 nanoparticles, which also reduces the magnetic properties. After mixing with water, YQ-2 and YQ-3 resins can be quickly separated from water under the action of a permanent magnet in just 30 seconds. The magnetic response effect is good, and the resin balls will quickly disperse again by gently shaking. In addition, there is no hysteresis in the magnetization curves of the resins, indicating that both YQ-2 and YQ-3 resins have superparamagnetism.
[0066] In order to further study the acid corrosion resistance of the synthesized magnetic resin microspheres YQ-2 and YQ-3, the resin microspheres were treated with hydrochloric acid of different concentrations for 12 hours and then the changes in magnetic properties were detected. Figure 7 (b) It can be seen that in the pH range of 2-5, YQ-2 and YQ-3 resins are stable, the saturation magnetization remains almost unchanged, and no iron is detected in the leachate. However, in a strong acidic environment, due to the corrosion of Fe3O4 nanoparticles, the saturation magnetization of YQ-2 and YQ-3 only decreased by 24% and 27%, respectively. It can also be seen from the figure that although the magnetism has decreased, there is no hysteresis in the magnetization curve, and the resin still has superparamagnetism.
[0067] 4. XRD analysis of resin The XRD diffraction patterns of the YQ-2 and YQ-3 magnetic resins prepared in Example 3 were measured using an X-ray powder diffractometer. The results are as follows: Figure 8 As shown in the figure, the double-layer oleic acid-modified Fe3O4 has diffraction peaks at 18.24°, 30.04°, 35.40°, 37.08°, 43.10°, 53.38°, 56.92° and 62.50°, corresponding to (111), (220), (311), (400), (422), (511), (440) and (533), which are Fe3O4 nanocrystalline structures with inverse spinel structures. The diffraction patterns of YQ-2 and YQ-3 resins are similar to those of oleic acid-modified Fe3O4, but the diffraction intensity is greatly weakened, indicating that the crystal structure in the resin comes from Fe3O4 nanoparticles, and the amination reaction and post-crosslinking reaction of the synthetic resin weaken the crystallinity of the nanomaterial. However, the diffraction peak of YQ-3 resin is weaker than that of YQ-2 resin, which is due to the strong acidic environment and swelling process of post-crosslinking that will corrode Fe3O4 nanocrystals.
[0068] 5. Infrared spectrum and XPS analysis of resin The infrared spectra of the YQ-1, YQ-2 and YQ-3 resins prepared in Example 3 were measured using an infrared spectrometer. The results are as follows: Fig. 9 (a). Fig. 9 (a) It can be seen that the three resins YQ-1, YQ-2 and YQ-3 have a peak at 570 cm -1 The Fe-O characteristic absorption peaks appeared on both sides, indicating that the Fe3O4 nanoparticles were successfully embedded and that all three resins had magnetic properties. -1 The characteristic peaks appearing around 3400cm are chloromethyl peaks. The peaks weakened after the chloromethyl groups of YQ-2 and YQ-3 resins undergo amination and post-crosslinking reactions. -1 and 1560cm -1 A new characteristic peak appeared around 1150cm -1 Characteristic peaks of CN bonds appear, and the appearance of these characteristic peaks proves the successful introduction of amine groups.
[0069] In order to further analyze the composition and morphology of the elements in the synthesized magnetic resin, XPS tests were performed on YQ-2 and YQ-3. The results are shown in Fig. 9 (b). In the energy spectrum of 0-1000eV, both YQ-2 and YQ-3 resins showed characteristic energy spectrum peaks of C1s, O1s and Fe2P, indicating that both resins contain carbon, oxygen and iron elements. YQ-2 resin also showed a characteristic energy spectrum peak of N1s at 399.8eV, indicating that ethylenediamine has been modified on YQ-2 resin. High-resolution scanning of N1s revealed an asymmetric peak shape, indicating the existence of multiple chemical forms. In order to analyze the form of N in the resin, the energy spectrum peak of N1s was fitted as shown in the following figure. Fig. 9 As shown in (c), the electron binding energy spectrum peaks of nitrogen appear at 399.25eV and 400.82eV respectively. The energy spectrum peak at 399.25eV is the characteristic peak of -NH or -NH2, and the energy spectrum peak at 400.82eV is the characteristic peak of protonated amine (-NH2 + or -NH3 + )’s characteristic peaks.
[0070] The above characterization results show that nano-Fe3O4 is synthesized by co-precipitation of iron and ferrous solution, oleic acid is added dropwise at the initial formation stage of Fe3O4 crystal phase, and secondary double-layer coating is used to make nano-Fe3O4 more stable, with better dispersion effect and corrosion resistance. TEM observation shows that the particle size of Fe3O4 nanoparticles modified with oleic acid is 8-15nm, and the diffraction pattern shows a nanocrystalline structure, with a saturation magnetization intensity of 31.5emu / g, and superparamagnetism.
[0071] Macroporous cross-linked precursor magnetic beads (YQ-1), amine-modified magnetic high cross-linked resin (YQ-2) and magnetic high cross-linked adsorption resin (YQ-3) were synthesized by suspension polymerization, suspension polymerization-amination-post-cross-linking, and suspension polymerization-post-cross-linking processes, respectively. Elemental analysis, FTIR spectrum and XPS spectrum analysis all showed that the three resins were successfully prepared. VSM analysis showed that the saturation magnetization of the three resins YQ-1, YQ-2 and YQ-3 were 3.04emu / g, 1.93emu / g and 1.72emu / g, respectively, all of which have superparamagnetism. Under acidic conditions, the saturation magnetization of YQ-2 and YQ-3 remained almost unchanged, and they have good acid corrosion resistance.
[0072] Example 5 Metal ion adsorption experiment 1. Heavy metal ion adsorption experiment Effect of Resin Addition Amount on Metal Ion Adsorption Performance Accurately weigh 0.01g, 0.02g, 0.05g, 0.10g, 0.20g and 0.40g of YQ-2 and YQ-3 resins, respectively, and place them in 150ml conical flasks, add 50ml of 1.0mmol / L adsorbent Cu(II) solution into the flask, set the pH value to about 4, the temperature to 298K, the speed to 150rpm, and perform oscillation reaction for 24h. After adsorption equilibrium, the concentration of Cu(II) in the solution is measured, the equilibrium adsorption amount and removal rate are calculated, and the effect of the amount of resin added on the adsorption of heavy metal ions in aqueous solution is investigated.
[0073] The adsorbents of the above solution were replaced with Pb(II) and Zn(II), the experiment was repeated, and the optimal amount of resin input for subsequent experiments was determined.
[0074] This experiment investigated the effect of the amount of YQ-2 resin added on the adsorption of heavy metal ions in aqueous solution. Fig.10 As shown in (a), with the increase of resin dosage, the removal rate of Cu(II) by YQ-2 resin also increases, and the removal rate of Cu(II) increases from 12.2% to 96.0%. This is because with the increase of adsorbent dosage, more adsorption sites can be provided per unit area to adsorb Cu(II). However, the equilibrium adsorption amount Q eHowever, it decreases with the increase of adsorbent dosage. This is because when the concentration of adsorbate Cu(II) remains unchanged, the active sites on the adsorbent can fully contact Cu(II) when less adsorbent is added. When more adsorbent is added, the active sites on the adsorbent can contact and squeeze each other, and some sites cannot be fully utilized. When the dosage of YQ-2 resin is less than 0.1g, that is, 2g / L, the removal rate of Cu(II) increases rapidly. When the dosage is greater than 0.1g (2 g / L), reaching 0.2g (4g / L) and 0.4g (8g / L), the removal rate of Cu(II) slows down. The removal rate and equilibrium adsorption capacity of YQ-3 resin for Cu(II) are significantly lower than those of YQ-2 resin. When the addition amount of resin reaches 0.4g, the removal rate of Cu(II) is only 15.3%, which indicates that the amine group on YQ-2 resin plays an important role in the adsorption of Cu(II). Although YQ-3 has a higher specific surface area and micropore area ratio, it has no complexing groups and can only weakly adsorb Cu(II) through cation-π bonds, while YQ-2 can also adsorb Cu(II) through the complexation between amine groups and Cu(II).
[0075] The effect of the amount of YQ-2 resin added on the adsorption of Pb(II) and Zn(II) is shown in Fig.10 (b). As the dosage of YQ-2 resin increases, the removal rates of Pb(II) and Zn(II) also increase, but the equilibrium adsorption capacity decreases, which is consistent with the adsorption law of Cu(II). When the dosage is greater than 0.1g (2g / L), the growth rate of the removal rate of Pb(II) and Zn(II) also shows a downward trend. Therefore, the addition amount of YQ-2 resin in subsequent experiments is selected as 2g / L.
[0076] 2. Effect of solution pH on adsorption performance Heavy metal ions generally form precipitation under alkaline conditions, which affects the adsorption effect. Therefore, the pH research range is set at pH2-6. Weigh 0.10g of YQ-2 and YQ-3 resins and place them in conical flasks respectively. Add 50ml of 1.0 mmol / L adsorbent Cu(II) solution to the flasks, and then adjust the pH of the solution with NaOH and dilute HNO3. Set the temperature to 298 K and the speed to 150rpm. Perform the oscillation reaction for 24h. After adsorption equilibrium, measure the concentration of Cu(II) in the solution and calculate the equilibrium adsorption amount.
[0077] The adsorbent of the above solution was replaced with Pb(II) and Zn(II), and the experiment was repeated to study the adsorption performance of the resin for heavy metal ions at different pH values.
[0078] Under different pH environments (pH=2-6), the adsorption of Cu(II), Pb(II) and Zn(II) in the solution by YQ-2 resin is shown in Figure 2. Fig.11 (a) The pH value of the water environment has a significant effect on adsorption. When the pH is 2, the adsorption of the three heavy metal ions by YQ-2 is very low. This is because in a lower pH environment, the H + The high concentration causes the amine groups on YQ-2 to protonate, generating electrostatic repulsion with heavy metal ions with the same charge, and H + It also competes with heavy metal ions for adsorption sites on YQ-2, so the adsorption amounts of Cu(II), Pb(II) and Zn(II) are very low. + The decrease in concentration weakens the site competition, and the deprotonation of the amine group of YQ-2 increases the electronegativity, weakening the electrostatic repulsion to heavy metal ions. At the same time, the amine groups on the resin are easy to complex with heavy metal ions to increase the adsorption amount. When the pH is greater than 5, the resin's adsorption of Cu(II) and Zn(II) remains almost unchanged, while the adsorption of Pb(II) is significantly reduced. This is mainly because heavy metal ions are prone to hydrolysis to varying degrees, and Pb(II) is easily precipitated at a higher pH, which reduces the adsorption amount. Therefore, in subsequent experiments, the pH value of YQ-2 adsorption of Cu(II) and Zn(II) was controlled at around 5, and the pH value of Pb(II) adsorption was controlled at around 4. The adsorption of Cu(II), Pb(II) and Zn(II) in the solution by YQ-3 resin is less than that of YQ-2 resin (see Fig.11 b) This is because there is no complexing group on the YQ-3 resin, and it mainly relies on the cation-π bond to adsorb heavy metal ions. The adsorption of the three heavy metal ions by the YQ-3 resin changes with pH value in a similar way to that of the YQ-2 resin. At low pH values, the H + Competition with heavy metal ion sites reduces the adsorption capacity. The adsorption capacity of YQ-3 resin for the three heavy metal ions is small.
[0079] 3. Effect of salt concentration on adsorption Prepare 100 ml of Cu(II)-NaNO3 and Cu(II)-Ca(NO3)2 solutions respectively, where the concentration of Cu(II) is constantly controlled at 1.0 mmol / L, and the concentration of Cu(II) and NO 3- The concentration ratio was controlled at 1:0, 1:10, 1:25, and 1:50, and then 0.20 g of YQ-2 resin and D001 (commercially purchased) resin were added to the solution. The initial pH value of the solution was controlled at about 5.0, the rotation speed was set to 150 rpm, and the temperature was set to 298 K for oscillation reaction for 24 hours. After the adsorption reached equilibrium, the concentration of Cu(II) in the solution was measured.
[0080] The experiment was repeated with the adsorbents of the above solution replaced with Pb(II) and Zn(II).
[0081] In fact, industrial wastewater containing heavy metals generally comes from industrial processes such as mining, smelting, papermaking, medicine and electronic electroplating. It not only contains a variety of heavy metal ions, but also often coexists with salts containing a variety of alkaline earth metal ions. The adsorption performance of the resin is disturbed, which increases the difficulty of heavy metal ion pollution control. A comparative study of the adsorption characteristics of YQ-2 and commercial D001 resin (commercially available) in saline wastewater provides theoretical guidance for the deep treatment of such industrial tail water with new magnetic cross-linked adsorption resins.
[0082] The adsorption of heavy metal ions by the resin when sodium salt and calcium salt coexist at different concentrations is as follows: Fig.12 As shown. Fig.12 (a) It can be seen that with the increase of sodium salt (NaNO3) concentration, the adsorption of Cu(II), Pb(II) and Zn(II) by YQ-2 increased, showing a salt-promoting effect that increased with the increase of salt concentration. The highest promotion rates for Cu(II), Pb(II) and Zn(II) reached 13.53%, 16.67% and 8.96%, respectively. This unique salt-promoting effect is the result of a combination of effects. On the one hand, the amino complex resin mainly adsorbs heavy metal ions through complexation. According to the theory of hard and soft acid-base, N as a hard base is easy to coordinate with heavy metal ions, while with Na + It is difficult to coordinate, Na + It will not compete with heavy metal ions for amine adsorption sites. On the other hand, the protonation of the amine groups on the resin and the adsorbed heavy metal ions will increase its positive charge, generating electrostatic repulsion on the heavy metals in the water, affecting adsorption, while the anions in the sodium salt can reduce the positive potential on the resin surface, making it easier for the heavy metal ions in the solution to diffuse to the resin surface, thereby increasing the adsorption amount.
[0083] Depend on Fig.12 (b) Comparative study results show that when YQ-2 resin coexists with sodium salt or calcium salt, both sodium salt and calcium salt can promote the adsorption of Cu(II) by YQ-2 resin. With the increase of salt concentration, the maximum promotion rate reaches 13.53% and 18.78%, respectively, indicating that the coexistence of inorganic salts promotes the adsorption of heavy metal ions by amino complex resins. The adsorption of Cu(II) by D001 commercial resin decreases with the increase of salt concentration, showing a negative salt effect. This is because D001 resin mainly adsorbs Cu(II) through ion exchange of sulfonic acid groups on the resin. The high concentration of Na in the coexisting salt can promote the adsorption of heavy metal ions by amino complex resins. + and Ca 2+ It can also occupy adsorption sites and be adsorbed onto the resin through ion exchange. This site competition and shielding effect lead to reduced adsorption of Cu(II). The coexistence of sodium salt and calcium salt inhibits the adsorption of Cu(II) by D001 resin. With the increase of salt concentration, the maximum inhibition rate reaches 46.53% and 54.78%, respectively. The inhibition rate of calcium salt is slightly higher than that of sodium salt, mainly because the sulfonic acid group on D001 resin has a higher ion charge than Ca(II).2+ The electrostatic attraction is greater, the adsorption thrust is stronger, and the inhibition effect is higher.
[0084] Example 6 Aromatic phenol adsorption experiment 1. The influence of resin addition amount on performance Accurately weigh 0.01, 0.02, 0.05, 0.10, 0.20g and 0.40g of YQ-2 and YQ-3 resins, add 50ml of 1.0mmol / L phenol, hydroquinone and p-nitrophenol solution respectively, set the pH value to about 6.5, the temperature and rotation speed to 298K and 150rpm respectively, carry out 24h of oscillation reaction, measure the concentration of phenol in the solution after the adsorption reaction is balanced, and then calculate the equilibrium adsorption amount and removal rate.
[0085] The effect of the dosage of YQ-2 and YQ-3 resins on the adsorption of three phenols was investigated. Fig.13 As shown in the figure, the results show that with the increase in the dosage of YQ-2 and YQ-3, the removal rates of phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP) all increase, but the equilibrium adsorption capacity decreases. This is because with the increase in the dosage of resin, the adsorbent per unit area can provide more adsorption sites to adsorb phenol, and the removal rate increases, but at the same time, with the increase in the number of adsorbents, the adsorbents will contact and squeeze each other, resulting in some adsorption sites not being fully utilized, resulting in a decrease in the equilibrium adsorption capacity.
[0086] When the dosage of the resin is less than 0.1g, i.e. 2g / L, the removal rate of phenol increases rapidly. When the dosage is greater than 0.1g (2g / L), the removal rate growth rate slows down, indicating that the competition for adsorption sites on the resin surface intensifies and the removal rate gradually tends to be flat. When the dosage of the resin is the same, the removal rate of the three aromatic phenols by YQ-3 resin is in the order of PNP>PN>HN, and the removal rate of the three phenols by YQ-2 resin is in the order of PNP>HN>PN. It is speculated that the reason for this difference is mainly related to the structure and properties of the adsorbate itself. The order of the removal rate of the three phenols by YQ-3 resin is consistent with the order of their hydrophobicity, while the order of the adsorption of the three phenols by YQ-2 resin is related to the hydrophobicity of the adsorbate, and may also be related to the affinity between the amine groups on the resin and the adsorbate.
[0087] 2. Effect of solution pH on phenol adsorption performance Weigh 0.10g of and YQ-3 resins respectively and place them in conical flasks, add 50ml of 1.0mmol·L-1 phenol, hydroquinone and p-nitrophenol solution into the flask, adjust the pH value with NaOH and dilute HCl, set the temperature and rotation speed at 298K and 150rpm respectively, and carry out 24h of oscillation reaction. After the adsorption reaction is balanced, measure the concentration of phenol in the solution, and then calculate the equilibrium adsorption amount.
[0088] The experiment tested the adsorption characteristics of YQ-3 resin on phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP) in solution under different environments (pH=2-6). The pH value of actual water bodies changes dynamically. Changes in pH value will cause changes in the morphology and structure of organic pollutants, and will also change the structure and surface electrical properties of polar groups on the resin. These changes will undoubtedly affect the adsorption performance and adsorption mechanism. The results are as follows Fig.14 As shown in the figure, there are two main adsorption mechanisms of YQ-3 resin for the three phenols: 1) hydrophobic effect, YQ-3 resin relies on van der Waals attraction to adsorb phenols; 2) there is a π-π force between the benzene ring of phenol and the benzene ring on the resin skeleton. When the pH is 2, the adsorption of the three phenols by YQ-3 resin is low, which is because a large amount of H+ in the solution can compete for the adsorption sites on the resin surface through the cation-π bond. As the pH value of the solution increases, the H+ concentration decreases and the adsorption amount gradually increases, but the growth rate slows down after the pH value is greater than 4. When the pH value is in the range of 2-6, the adsorption of the three phenols by YQ-3 increases with the increase of pH value. At this time, the order of the adsorption of the three aromatic phenols by YQ-3 resin is PNP>PN>HN. However, under acidic conditions (pH 2), the resin has the largest adsorption of PN, which may be due to the inhibition of hydrophobic effect in a strong acidic environment, and PN with the highest solubility is easier to be adsorbed on the resin surface. When pH>7, the adsorption of PNP begins to decrease, the proportion of PNP-anion increases, the ratio of molecular PNP0 decreases, the hydrophilicity of nitrophenol increases, and the hydrophobic effect weakens, resulting in a decrease in adsorption. When pH>8, the adsorption of phenol and hydroquinone begins to decrease. At this time, the ratio of phenol and hydroquinone anions gradually increases, the hydrophobic effect is inhibited, and the adsorption begins to decrease.
[0089] The experimental test studied the adsorption characteristics of YQ-2 resin on phenol (PN), hydroquinone (HN), and p-nitrophenol (PNP) in solution under different pH environments (pH=2-6). The results are as follows Fig.14(b) Studies have shown that the adsorption of phenolic compounds by YQ-2 resin involves the following adsorption effects: 1) hydrophobic effect and π-π effect; 2) hydrogen bonding effect between amine groups on the resin and phenolic hydroxyl groups; 3) electrostatic adsorption effect between protonated amine groups and imine groups on the resin and anionic phenols. When the pH is 2, the adsorption of the three phenols by YQ-2 resin is very low. The high concentration of H+ competes for adsorption sites and simultaneously causes the amine groups on YQ-2 to protonate. The hydrophobic effect and hydrogen bonding effect are inhibited, and the adsorption amount is very low. When the pH increases from 2 to 5, the adsorption of the three phenols by YQ-2 resin increases rapidly. The order of the adsorption of the three aromatic phenols by YQ-2 resin is PNP>HN>PN. PNP has the highest adsorption amount. Although PN is more hydrophobic than HN, HN contains two hydroxyl groups in its structure. The hydrogen bonding effect between the amine groups on the resin and the hydroxyl groups on HN is stronger than that with PN. The combined effect results in a higher adsorption amount of HN. When the pH increases from 5 to 7, the three phenols exist in molecular state and a small amount of anionic state. The resin adsorbs phenols through hydrophobic, hydrogen bonding and electrostatic effects, and the adsorption amount increases slightly. When the pH>7, the adsorption amount begins to decrease. At this time, the proportion of phenol anionic state increases, and the proportion of molecular state decreases, which inhibits the hydrophobic and hydrogen bonding effects. The potential of the resin decreases, the electrostatic effect weakens, and the adsorption amount decreases. After pH>9, the adsorption amount of the three phenols by the resin decreases significantly. This is because the zeta potential of the resin is negative at this time, and the phenol is mainly in anionic state. The electrostatic repulsion between the resin and the phenol inhibits adsorption.
[0090] 3. Effect of inorganic salts on adsorption performance Prepare 100 ml of PN-NaCl solution respectively, in which the concentration of adsorbent PN is constantly controlled at 1.0 mmol / L, and the concentration of NaCl is controlled at 0, 2%, 4%, 8%, 15%, and 20%. Then add 0.20 g of YQ-2 or YQ-3 resin to the solution, control the initial pH value of the solution at about 5.0, set the temperature and rotation speed at 298 K and 150 rpm respectively, and carry out 24 hours of oscillation reaction. After the adsorption reaches equilibrium, measure the concentration of PN in the solution and calculate the equilibrium adsorption amount.
[0091] The adsorbents of the above solution were replaced with PNP and HN, and the experiment was repeated.
[0092] In actual phenol-containing wastewater, in addition to aromatic phenol organic pollutants, it often also contains a certain concentration of inorganic salts. These inorganic salt ions may compete with phenol pollutants for adsorption sites or produce a "salting-in" effect to inhibit adsorption. They may also combine with resins or promote adsorption through a "salting-out" effect, and the adsorption mechanism is more complicated.
[0093] When coexisting with different concentrations of NaCl, the adsorption performance of YQ-2 resin for PN, HN and PNP is as follows: Fig.15 As shown. Fig.15It can be seen that with the increase of sodium chloride concentration, the adsorption of PN, HN and PNP by YQ-2 resin first slightly decreased and then gradually increased. When the concentration of NaCl in the solution increased from 0 to 8%, the adsorption of PN, HN and PNP first slightly decreased, with the highest decrease rates of 5.12%, 6.26% and 6.83%, respectively. YQ-2 resin adsorbs phenolic pollutants through the comprehensive effects of hydrophobicity, π-π, hydrogen bonding and electrostatics. - The adsorption sites on YQ-2 can be competed for by electrostatic action, which also proves that there is an electrostatic mechanism in the adsorption process, but this effect is not strong. When the concentration of NaCl exceeds 8%, the adsorption of phenols by YQ-2 begins to increase. This is mainly due to the increase in the concentration of sodium chloride, the solubility of phenolic compounds in aqueous solution is inhibited, the hydrophobic effect is enhanced, and the diffusion of adsorbate to the surface of the resin is promoted. The electrostatic mechanism is weakened, and the "salting out" effect of high concentration of NaCl promotes the adsorption of phenolic pollutants and the adsorption amount increases. Overall, the coexistence of inorganic salts has no significant effect on the adsorption of phenolic compounds on YQ-2 resin.
[0094] The adsorption of PN, HN and PNP by YQ-3 resin gradually increased with the increase of NaCl concentration, and the maximum growth rates of adsorption of PN, HN and PNP were 9.29%, 11.84% and 7.93%, respectively. YQ-3 resin adsorbs phenolic pollutants through hydrophobic and π-π effects. With the increase of salt concentration, the "salting out" effect enhances the hydrophobic mechanism and promotes adsorption. It can be seen that YQ-2 magnetic cross-linked adsorption resin is little disturbed by the change of coexisting salt concentration and can be used for the efficient removal of aromatic phenol pollutants in actual saline water bodies.
[0095] Example 7 Adsorption and removal experiment of metal ion and aromatic phenol composite pollution 1. Adsorption of Cu(II)-PNP composite pollutants by YQ-2 under different pH conditions Weigh 0.10g of YQ-2 resin and place them in conical flasks, add 50ml of Cu(II) and PNP mixed solution into the flask, the initial concentration of Cu(II) and PNP is 1.0mmol·L-1, and then adjust the pH of the solution to 2-7 with NaOH and dilute HNO3. Set the temperature and rotation speed to 298K and 150rpm respectively, and carry out 24h oscillation reaction. After the adsorption reaches equilibrium, measure the concentrations of Cu(II) and PNP in the solution, and then calculate the equilibrium adsorption amount.
[0096] The adsorption of Cu(II) and PNP in single component and composite systems by YQ-2 resin under different pH environments (pH 2-6) is shown in the following table. Fig.16As shown. The results show that the curve in the Cu(II)-PNP composite system is similar to that of the single component, and the adsorption amount of Cu(II) in the two systems is consistent with the change of pH. In a low pH environment, H+ causes the amine group on YQ-2 to protonate, and H+ competes for adsorption sites. The adsorption amount of Cu(II) in both systems is very low. With the increase of pH value, the amine complexation is enhanced and the adsorption amount increases. Under the same pH conditions, the adsorption amount of Cu(II) in the composite system is higher than that in the single component system. The coexistence of PNP can promote the adsorption of Cu(II) by YQ-2. At this time, there are several mechanisms in the coexistence system (see Table 1 for the mode of action): (1) Cu(II) and PNP compete for the amine adsorption sites on the resin (A1, B2, B3); (2) PNP adsorbed on the resin provides new adsorption sites for Cu(II), and adsorbs Cu(II) through the phenolic hydroxyl complex on PNP (C1); (3) Cu(II) and PNP in the aqueous phase undergo complexation to form a Cu(II)-PNP complex, which is adsorbed by YQ-2 (C2). The competitive and assisted adsorption mechanisms work together. It is speculated that the affinity between the amine group on the resin and Cu(II) is stronger than that between PNP, and the site competition of PNP has little effect on Cu(II) within the pH range studied. Both mechanisms C1 and C2 can promote the adsorption of Cu(II), and a small amount of anionic PNP- in the system can neutralize the positive charge of YQ-2 and reduce the electrostatic repulsion between YQ-2 and Cu(II). The above combined effects increase the adsorption of Cu(II) by YQ-2 in the composite system.
[0097] The adsorption of PNP in the composite system is consistent with that of the single component. At low pH, the adsorption of PNP is low. As the pH increases, YQ-2 adsorbs PNP through hydrophobic, hydrogen bonding and electrostatic synergistic adsorption, and the adsorption increases.
[0098] 2. Preload adsorption experiment 1) Adsorption of Cu(II) by PNP preload Weigh 0.20g YQ-2 resin and place it in a conical flask, add 100ml of PNP solution with different initial concentrations (0-4.0mmol·L-1), adjust the pH value of the solution to about 5.0, set the temperature and speed to 298K and 150rpm, and perform 24h oscillation reaction to obtain five groups of YQ-2-PNP resins with different loading concentrations, filter them again, put them into a conical flask after drying, add 100ml of Cu(II) solution with concentrations of 0.5mmol / L and 3mmol / L, respectively, adjust the pH value to about 5.0, set the temperature and speed to 298K and 150rpm, and perform 24h oscillation reaction. After the adsorption reaches equilibrium, calculate the adsorption amount of Cu(II) in the solution, and perform a control experiment with YQ-2 resin without PNP loading. The experimental results are shown in 17.
[0099] Fig.17 First, the YQ-2 resin was pre-adsorbed with different concentrations (0-4.0mmol / L) of Cu(II) solution, and then the changes in the adsorption amount of PNP by YQ-2-Cu(II) resin were investigated, and the performance of PNP adsorption by unloaded fresh resin was compared. As shown in 17 (a), the equilibrium adsorption amount of PNP with an initial concentration of 0.5mmol / L increased with the increase of the pre-adsorption amount of Cu(II). When the pre-adsorption amount of Cu(II) reached 0.92mmol / g, the maximum growth rate of PNP adsorption reached 8.06%. At this time, the pre-adsorbed Cu(II) was mainly adsorbed through the complexation of the amine group, occupying the hydrophilic amine site. At this time, the concentration of PNP added was very low, only 0.5mmol / L. It was adsorbed on the resin through hydrophobic and π-π effects, and saturated adsorption could be performed by occupying the hydrophobic site. Competition for the amine site was not the main mechanism. The gradual increase in the amount of PNP adsorption indicates that the pre-adsorbed Cu(II) provides a new site for the adsorption of PNP through bridging, forming a YQ-2-Cu(II)-PNP ternary complex. During the adsorption of PNP by YQ-2-Cu(II) resin, almost no free Cu(II) was detected in the aqueous phase, which indicates that the Cu(II) pre-adsorbed on the YQ-2 resin was not released into the aqueous phase, and it is difficult for PNP to replace the Cu(II) on the YQ-2 resin. The complexation between the amino group on the YQ-2 resin and Cu(II) is stronger than the hydrogen bonding between PNP and YQ-2 resin.
[0100] from Fig.17(b) It can be seen that the equilibrium adsorption amount of PNP with an initial concentration of 3.0mmol / L first increases and then decreases with the increase of the pre-adsorption amount of Cu(II). When the pre-adsorption amount of Cu(II) is less than 0.4mmol / g, the PNP adsorption amount increases slightly. At this time, the added PNP concentration is relatively high, reaching 3mmol / L. However, the loading amount of Cu(II) is low at this time. There are a large number of hydrophobic sites on the resin, and a large number of hydrophilic amine sites are not occupied. Site competition has little effect on PNP adsorption. At the same time, the pre-adsorbed Cu(II) promotes the adsorption of PNP through bridging. When the pre-adsorption amount of Cu(II) is greater than 0.65mmol / g, the PNP adsorption amount begins to decrease. At this time, the amine sites on the YQ-2 resin are occupied by more Cu(II), and the affinity between the amine and Cu(II) is stronger, which will inevitably lead to a decrease in the sites available for PNP adsorption. Although the pre-adsorbed Cu(II) can adsorb a small amount of PNP through bridging, the concentrations of Cu(II) and PNP are both high at this time, and the site competition is dominant, resulting in a decrease in the amount of PNP adsorption. During the adsorption of PNP by YQ-2-Cu(II) resin, only a trace amount of free Cu(II) (less than 0.01mmol / L) was detected in the aqueous phase, indicating that even with high concentrations of PNP competitive adsorption, it is difficult to replace the Cu(II) pre-adsorbed on the resin, which once again proves that the affinity between the amino group on the YQ-2 resin and Cu(II) is stronger than that of PNP.
[0101] 2) Adsorption of PNP by Cu(II) preload Weigh 0.20g YQ-2 resin and place it in a conical flask, add 100ml of Cu(II) solution with different initial concentrations (0-4.0mmol·L-1) respectively, adjust the pH value of the solution to about 5.0, set the temperature and rotation speed to 298K and 150rpm respectively, and perform 24h oscillation reaction to obtain five groups of YQ-2-Cu(II) resins loaded with different concentrations. Filter again, put it into a conical flask after drying, add 100ml of PNP solution with concentrations of 0.5mmol / L and 3mmol / L respectively, adjust the pH value to about 5.0, set the temperature and rotation speed to 298K and 150rpm respectively, and perform 24h oscillation reaction. After adsorption equilibrium, calculate the adsorption amount of PNP in the solution, and carry out a control experiment with fresh resin without Cu(II) loading. The results are as follows: Fig.18 shown. Fig.18 The YQ-2 resin was first pre-adsorbed with PNP solutions of different concentrations (0-4.0mmol / L), and then the changes in the adsorption amount of Cu(II) by YQ-2-PNP resin were investigated and compared with the adsorption performance of Cu(II) by fresh unloaded resin.
[0102] As shown in Figure 18 (a), the equilibrium adsorption amount of Cu(II) with an initial concentration of 0.5 mmol / L first decreases and then increases with the increase of the pre-adsorption amount of PNP. The adsorption amount is higher when the PNP is loaded with a high concentration than that of the fresh resin without loading. When the pre-adsorption amount of PNP is small, the above mechanism (1) (3) is weak, and the pre-adsorbed PNP occupies the amine site. The low concentration of Cu(II) competes for the amine site, and the adsorption amount decreases. As the pre-adsorption amount of PNP increases, the effects of (1) (3) are enhanced, and the phenolic hydroxyl groups on the high concentration of PNP can provide a large number of new sites to adsorb low concentrations of Cu(II), and the adsorption amount increases.
[0103] As shown in Figure 18 (b), when the initial concentration of the added Cu(II) is 3.0 mmol / L, the equilibrium adsorption amount of Cu(II) first decreases and then increases with the increase of the pre-adsorption amount of PNP, but the adsorption amount is always lower than that of the unloaded fresh resin, and is accompanied by an increase in the release amount of PNP detected in the aqueous phase. At this time, the concentration of Cu(II) is high, and the competitive effect of the above mechanism (2) is dominant. Cu(II) competes with PNP for the amino site. Although mechanisms (1) and (3) promote adsorption and increase the adsorption amount, they are not enough to compensate for the decrease in adsorption caused by mechanism (2). As the amount of PNP pre-adsorbed increases, more amine sites are occupied, and Cu(II) competes with PNP to adsorb hydrophilic amine sites to replace part of PNP. PNP adsorbed by hydrophobic adsorption can provide a large number of new adsorption sites, and the adsorption of Cu(II) begins to increase. However, at this time, the concentration of Cu(II) is high, and the PNP on the loaded resin can only effectively adsorb part of Cu(II), so the adsorption of Cu(II) is always lower than that of the unloaded fresh resin, which also indicates that the affinity of the phenolic hydroxyl group on PNP for Cu(II) may be smaller than that of the amine group. At the same time, PNP was detected in the aqueous phase, and part of the PNP pre-adsorbed on the amine group of the resin hydrophilic site was replaced by Cu(II) and released into the aqueous phase. It proves that the complexation between the amine group and Cu(II) is stronger than the hydrogen bond and electrostatic interaction between the amine group and PNP.
[0104] 3. Isothermal equilibrium adsorption Adsorption of Cu(II) in Cu(II)-PNP composite system: Weigh 0.20 g YQ-2 resin and place it in a conical flask, add 100 ml of mixed solution of Cu(II) and PNP respectively, control the initial concentration of Cu(II) to (0-4.0 mmol / L), control the concentration of coexisting PNP in the composite system to (0.5 mmol / L, 3 mmol / L-1), adjust the pH value of the solution to about 5.0, set the temperature and rotation speed to 298 K and 150 rpm respectively, carry out 24 h oscillation reaction, and calculate the equilibrium adsorption amount of Cu(II) after adsorption equilibrium.
[0105] Adsorption of PNP in Cu(II)-PNP composite system: Weigh 0.20 g YQ-2 resin and place it in a conical flask, add 100 ml of mixed solution of Cu(II) and PNP respectively, control the initial concentration of PNP to (0-4.0mmol / L), control the concentration of coexisting Cu(II) in the composite system to (0.5mmol / L, 3mmol / L), adjust the pH value of the solution to about 5.0, set the temperature and rotation speed to 298 K and 150 rpm respectively, carry out 24h oscillation reaction, and calculate the equilibrium adsorption amount of PNP after adsorption equilibrium.
[0106] The adsorption isotherms of YQ-2 resin for Cu(II) and PNP in the composite system are shown in Fig.19 The isothermal adsorption process was fitted by the Freundlich and Langmuir models, and the specific parameters are shown in Table 2. Comparing the fitting coefficients (R2) and root mean square error (RMSE) of the two models in Table 2, it was found that the adsorption data of Cu(II) in the composite system by YQ-2 was fitted by the Langmuir model with a higher R2 value and a lower RMSE value. This indicates that the adsorption process is a monolayer adsorption, which is consistent with the conclusion drawn from the adsorption of single-component Cu(II) by YQ-2. The order of Qmax and KF values of Cu(II) is: composite system (PNP 3.0mmol / L)>composite system (PNP 0.5mmol / L)>single-component Cu(II). When the concentration of PNP in the composite system reaches 3.0mmol·L-1, the saturated adsorption amount of Cu(II) increases by 17.64% compared with the single-component system, indicating that the coexistence of PNP can promote the adsorption of Cu(II) by YQ-2.
[0107] The phase R2 value of the Freundlich model of PNP adsorption by YQ-2 resin in the composite system is higher and the RMSE value is smaller, which is considered to be a heterogeneous multilayer adsorption process, which is consistent with the adsorption conclusion of single-component PNP. The index n is greater than 1, which is a preferential adsorption process. Although the parameters of the Langmuir model fitting are lower than those of Freundlich, the R2 values are also greater than 0.97, and the fitted parameter values can also be used to analyze the adsorption process. The order of characteristic parameters KF and Qmax is: single component > composite system (Cu(II) is 0.5mmol / L) > composite system (Cu(II) is 3.0mmol / L). The coexistence of Cu(II) in the composite system inhibits the adsorption of PNP by YQ-2 resin. When the coexisting Cu(II) is 0.5mmol / L, the inhibition rate is only 2%, and when the coexisting Cu(II) is 3.0mmol / L, the inhibition rate reaches 19.8%. The higher the concentration of Cu(II) in the composite system, the stronger the inhibitory effect on PNP adsorption, which is mainly due to the competition for amine sites. The coexistence of Cu(II) will inhibit the adsorption of PNP by YQ-2, and the inhibitory effect is not significant at low concentrations, which is particularly suitable for the common situation of metal ion pollution in water environment.
[0108] Table 2. Langmuir and Freundlich isotherm model parameters for Cu(II) and PNP adsorption on YQ-2 resin PNP on YQ-2 4. Recycling experiment The used YQ-2 resin was filtered and then desorbed by infiltration with 0.2 mol / L and 0.5 mol / L HCl solutions. The desorbed and regenerated YQ-2 resin was washed and filtered, and a Cu(II)-PNP mixed solution with an initial concentration of 1.0 mmol / L was added again. The equilibrium adsorption capacity of Cu(II) and PNP on the desorbed and regenerated resin was calculated. The adsorption-desorption experiment was repeated 10 times to verify the regeneration stability of the YQ-2 resin.
[0109] Changes in the pH value of the solution will cause changes in the morphology and structure of the adsorbate pollutants, and will also change the structure and electrical properties of the polar groups on the resin. Therefore, the pH value of the water body is an important factor affecting the adsorption effect. Previous studies have found that in a strong acidic environment, the adsorption performance of YQ-2 magnetic cross-linked resin for adsorbates Cu(II) and PNP is weak. We filtered the used YQ-2 resin and then soaked it with HCl solution for desorption. We found that the adsorbed Cu(II) and PNP can be well desorbed from the YQ-2 resin. The greater the acidity, the higher the desorption amount. When the concentration of HCl is 0.2mol / L, the desorption rates of Cu(II) and PNP are 97.8% and 94.1%, respectively; when the concentration of HCl reaches 0.5mol / L, the desorption rates of Cu(II) and PNP are 98.7.0% and 95.2%, respectively.
[0110] In order to further study the adsorption performance of YQ-2 resin after desorption on Cu(II) and PNP in water, the YQ-2 resin soaked with 0.2 mol / L hydrochloric acid was washed and filtered, and a Cu(II)-PNP mixed solution with an initial concentration of 1.0 mmol / L was added again. The adsorption amount of Cu(II) and PNP by YQ-2 resin after desorption and regeneration was calculated. The results are shown in Figure 2. Fig. 20 As shown. Fig. 20 It can be seen that in the 10-cycle adsorption-desorption experiment, the adsorption amount of Cu(II) and PNP by YQ-2 resin hardly decreased in the first 6 times, and the adsorption performance decreased after the 6th time. After 10 cycles, the decrease rates of Cu(II) and PNP were 4.43% and 6.74%, respectively. The decrease in adsorption rate may be due to the fact that after repeated infiltration of hydrochloric acid, a small number of adsorption sites were occupied by H+ or lost. However, in general, YQ-2 magnetic cross-linked adsorption resin has good desorption and regeneration performance and good stability in practical applications.
Claims
1. A method for preparing a magnetic aminated highly cross-linked adsorption resin, characterized in that: The following steps are involved: 1) Dissolve ferric chloride hexahydrate and ferric chloride tetrahydrate in deionized water, heat to 70-90°C, add ammonia water, and drop acetone mixed with oleic acid to react for 5-15 minutes, then drop oleic acid to react, and separate the monolayer oleic acid-modified Fe3O4 nanoparticles after the reaction is complete; 2) Mix the monolayer oleic acid-modified Fe3O4 nanoparticles with ammonia water, add oleic acid under nitrogen atmosphere, heat to 70-90°C, react for 25-35 minutes, cool and add a small amount of dilute hydrochloric acid for precipitation and separation to obtain double-layer oleic acid-modified Fe3O4 nanoparticles; 3) Mixing a dispersed phase consisting of an aqueous solution of gelatin, polyvinyl alcohol, sodium sulfate and lauryl sulfuric acid with an oil phase consisting of divinylbenzene (DVB), double-layer oleic acid-modified Fe3O4 nanomagnetic beads, porogen n-hexane and initiator benzoyl peroxide, stirring at 70-90°C under nitrogen protection, and performing a suspension polymerization reaction. After the reaction is completed, cooling and separating the precipitate, washing the solid with hot water, and drying to obtain a magnetic cross-linked resin; 4) The magnetic cross-linked resin obtained in the previous step is swollen in toluene, and then ethylenediamine solution is added, stirred, and heated to 60-70° C., and the reaction is completed to obtain a magnetic aminated cross-linked resin; 5) After swelling the magnetic aminated cross-linked resin in 1,2-dichloroethane, add FeCl3, stir and reflux at 60-70°C for 0.5-2 hours, then raise the temperature to 80-90°C, continue stirring and reflux reaction for 4-6 hours, and after the reaction is completed, cool and separate to obtain a magnetic aminated highly cross-linked adsorption resin.
2. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 1), the temperature after heating is 80°C, the oleic acid dropping rate is 1g / 5min, and the reaction is carried out for at least 30min after the oleic acid is added.
3. The method for preparing a magnetic aminated highly cross-linked adsorption resin according to claim 1, wherein in step 1), Fe 2+ :Fe 3+ The molar ratio of Fe is 1:
2. 2+ : The molar ratio of to ammonia water is 5:(1-2).
4. The method for preparing a magnetic aminated highly cross-linked adsorption resin according to claim 1, wherein in step 1), the mass ratio of oleic acid to ferric chloride tetrahydrate is 1:1, wherein: The mass ratio of the oleic acid in the acetone to the oleic acid subsequently added dropwise is 1:
4.
5. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 2), the amount of oleic acid is equivalent to the total amount of oleic acid added in step 1).
6. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 2), the reaction temperature is 80°C and the reaction time is 30 min.
7. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 3), the weight ratio of the dispersed phase, gelatin, polyvinyl alcohol, sodium sulfate and lauryl sulfuric acid is 2:2:0.1:0.1; the weight ratio of the oil phase, chloromethylstyrene, divinylbenzene, double-layer oleic acid-modified Fe3O4 nano-magnetic beads, n-hexane and benzoyl peroxide is 45:5:4:30:0.
6.
8. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 4), the mass volume ratio of the magnetic cross-linked resin to ethylenediamine is 1:4 g / ml.
9. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 4), the reaction temperature is 62°C and the reaction time is 6 hours.
10. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 5), the mass ratio of the magnetic cross-linked resin to FeCl3 is 25:
3.
11. The method for preparing a magnetic aminated highly cross-linked adsorption resin as claimed in claim 1, wherein in step 5), FeCl3 is added, and the mixture is stirred and refluxed at 62°C for 1 hour, then the mixture is heated to 90°C and stirred and refluxed for 5 hours. After the reaction is completed, the mixture is cooled, the resin is separated, washed to neutrality, and dried.
12. The method for preparing a magnetic aminated highly cross-linked adsorption resin according to claim 1, wherein in step 5), a sodium hydroxide solution is further added to neutralize the HCl produced by the reaction.
13. Use of the magnetic aminated highly cross-linked adsorption resin prepared by the preparation method of any one of claims 1 to 12 for adsorbing and removing heavy metal ions and / or aromatic phenol pollutants, or for adsorbing and removing heavy metal ions and aromatic phenol composite pollutants in water.
14. The use according to claim 13, wherein the heavy metal ions are one or more of Cu(II), Pb(II) and Zn(II), and the aromatic phenols are one or more of phenol, hydroquinone and p-nitrophenol.
Citation Information
Patent Citations
Cross-linking adsorbent resin with ultrahigh magnetic property and preparation method thereof
CN102049243A
A method for preparing a polyethylenepolyamine-modified ultra-high crosslinked adsorption resin
CN102276766A
Magnetic chelating resin, preparation method and application thereof in purification of compound polluted water
CN108047361A
Pyridyl modified composite function super high crosslinked adsorptive resin and its preparing method
CN1858088A
Composite functional super high cross-linked adsorption resin containing quaternary amine group, and its preparation method
CN1865302A
